Twentieth century artists on art (Pantheon Books, 1985)
"A sequel to Goldwater and Treves's classic Artists on Art ... lets us see modern art through the eyes of those who created it. Ashton brings together statements by over two hundred of the foremost modern artists from all over the Western world, describing their views of art and their own work."--Back cover.